THE USE OF AUDIO-VISUAL MEDIA IN ISLAMIC RELIGIOUS EDUCATION TO IMPROVE STUDENTS’ ACADEMIC ACHIEVEMENT AT MIN DENPASAR - doadi, doadi (Erudio Journal of Educational Innovation, 2025)
This study aims to analyze the effectiveness of using audio-visual media in teaching Islamic Religious Education (PAI) at MIN Denpasar and to examine its impact on improving students' academic achievement and religious character. The background of this research arises from the challenges of teaching Islamic studies in the digital era, which is still largely dominated by conventional lecture methods that tend to reduce students’ motivation and understanding of Islamic values. Audio-visual media is considered an innovative solution that integrates sound and imagery to stimulate the two main learning senses—hearing and sight—simultaneously.This study employed a qualitative approach with a phenomenological design. Data were collected through non-participatory observation, in-depth interviews with the school principal, Islamic education teachers, and students, as well as documentation of student learning outcomes. The data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, supported by triangulation of sources and methods to ensure data validity.The findings show that the use of audio-visual media creates a more lively, interactive, and communicative learning atmosphere. Students were able to understand abstract concepts such as faith and the stories of the prophets more easily and showed greater enthusiasm and active participation in the learning process.